Revision of the South American freshwater genus Plagioscion (Teleostei, Perciformes, Sciaenidae) - Casatti, Lilian [UNESP] (My University, 2005)
The South American freshwater sciaenid genus Plagioscion is reviewed. Five of the 15 nominal species assigned to the genus are considered to be valid: Plagioscion squamosissimus, widely distributed in Atlantic drainages east of the Andes; P. auratus from the Río Orinoco and Río Amazonas basins; P. magdalenae from the Río Magdalena and Río Amazonas basins; P. ternetzi from the lower Río Paraná, Río Paraguay and Rio Uruguay basins; and P. montei from the Río Amazonas basin. Copyright © 2005 Magnolia Press.
Keywords: Freshwater sciaenidae; Plagioscion; South America; Taxonomy; Perciformes; Plagioscion auratus; Plagioscion squamosissimus; Sciaenidae; Teleostei